Protection and Rational use of Water Resources - Shakhodatkhon, Samirsakova; qizi, Pulatova Shakhnoza Valijon; ogli, Kamchiboyev Mukhammad Qodir Ibrokhimjon; ogli, Kimsanboyev Izzatillo Rustamjon; ogli, Mukhammadjanov Jakhongir Sherali (Indonesian Journal of Public Policy Review, 2022)
If astronomers want to know if there is life on another planet, they first begin to determine if there is water on that planet. Because in order for life to exist, water must first exist. Science has already proved that life on Earth first appeared in water and passed from it to land - air and soil. Water, with its solubility, sustains the life of all living organisms in nature. Academician AP Karpinsky, the father of Russian geology, wrote, "Water is the most precious resource, and it is impossible to live without it.